The Utilization Of Local Food Materials In Food Bars For Disaster Resilience Amidst Modern Transformation - Durry, Fara Disa; Prasetya, Johan Danu; Sahadewa, Sukma; Windyantini, Hanna; Winata, Lionesya Sukma; Artha Putri, Awanda Dias Rizkia (Green Publisher Indonesia, 2024)
Indonesia is a country that is prone to natural disasters. Landslide disaster are the 3rd highest disaster intensitas in Indonesia that happened in 2020. According to data from the National Disaster Management Agency (BNPB), Indonesia experienced 12,254 disasters during the period 2015 to 2019. Various kinds of disasters such as floods, tsunamis, earthquakes, volcanic eruptions occur and usually have impacts that make it difficult for people to get aid, one of which is food. Providing emergency food easy to consume and contains high calories is important to do and to increase the nation's food security. The development of emergency food based on local products has been widely explored. Method The study is a literature review with the keywords food resilient, landslides, emergency food product, food bars in several databases such as proquest, science direct, pubmed, and google scholar.Result The study aimed to review food bars as food resilient using lokal food ingredients during landslide disaster.